Caring : a relational approach to ethics & moral education - Noddings, Nel (University of California Press, 2013)
With numerous examples to supplement her rich theoretical discussion, Nel Noddings builds a compelling philosophical argument for an ethics based on natural caring, as in the care of a mother for her child. In Caring--now updated with a new preface and afterword reflecting on the ongoing relevance of the subject matter--the author provides a wide-ranging consideration of whether organizations, which operate at a remove from the caring relationship, can truly be called ethical. She discusses the extent to which we may truly care for plants, animals, or ideas. Finally, she proposes a realignment of education to encourage and reward not just rationality and trained intelligence, but also enhanced sensitivity in moral matters." --